Operative techniques in orthopaedic surgical oncology - Malawer, Martin M.; Wittig, James C.; Bickels, Jacob (Philadelphia : Wolters Kluwer, 2021)
"Derived from Sam W. Wiesel and Todd Albert's four-volume Operative Techniques in Orthopaedic Surgery, this single-volume resource contains the user-friendly, step-by-step information you need to confidently perform the full range of operative techniques in surgical oncology. In one convenient place, you'll find the entire Oncology section. Superb full-color illustrations and step-by-step explanations help you master surgical techniques, select the best procedure, avoid complications, and anticipate outcomes. Written by global experts from leading Operative Techniques in Orthopaedic Surgical Oncology, Third Edition, provides authoritative, easy-to-follow guidance to both the novice trainee or experienced surgeon"--